Menjelajahi SCM di Dunia Game: Studi Kasus Growtopia - Muhamad Paturahman; Achmad Syamsudin; Gema Borneo Poetra; Nurlia Eka Damayanti (JURISMA : Jurnal Riset Bisnis & Manajemen, 2025)
This study explores the distribution mechanisms within the virtual world of the online multiplayer game Growtopia and investigates their relevance to real-world supply chain management (SCM) practices. Using a qualitative case study approach, data were collected through in-depth interviews and virtual observation of player activities. The research identifies how virtual economies, player-driven logistics, and peer-to-peer transactions in Growtopia replicate fundamental SCM processes, including sourcing, inventory management, distribution, and end-user satisfaction. Furthermore, the study reveals that certain digital strategies used in the game, such as automated vending systems and community-based trust networks can inspire innovative SCM practices in digital commerce. The findings highlight the potential of game-based simulations as tools for SCM learning, experimentation, and adaptation in dynamic, digital environments. Keywords : Virtual Supply Chain; Growtopia; Game-based Simulation; Distribution Strategy; Supply Chain Management; Digital Economy